An Academic Innovation: The Executive Ph.D. in Urban Higher Education at a Historically Black University. Issue 168 (June 2016) - Stevenson, Joseph Martin; Payne, Alfredda Hunt
Abstract : This chapter describes how data analysis and data‐driven decision making were critical for designing, developing, and assessing a new academic program. The authors—one, the program's founder; the other, an alumna—begin by highlighting some of the elements in the program's incubation and, subsequently, describe some of the components for data management that are required for program quality. The chapter is divided into the following six sections: historically Black colleges and universities (HBCUs) and the EPhD; mission of the EPhD; program overview, objectives, and implementation; alignment and first cohort experiences; and the role of institutional research. In short, institutional research serves a central role in the design, development, and success of this innovative program.